SKEMA MANDHÊG DALAM STRUKTUR GENDHING GAYA SURAKARTA - Ananto Sabdo Aji (Institut Seni Indonesia Surakarta, 2020)
This thesis reveals mandhêg as one of the local concepts of Javanese music, especially the Surakarta style. Several issues to be explored are related to the mandhêg scheme in each musical structure. The data collection was carried out by literature study, interviews, and also as a participant observer. The analysis is carried out by reinterpreting the thoughts and experience of the pêngrawit through pragmatic reality. The interpretation uses interpretation method and garap analysis. The explanation and getting conclusions are carried out by the inductive method. Each mandhêg structure has a different mandhêg location or position, there is a mandhêg location that has become an optional convention or standard, there is also a mandhêg gawan which must be presented, pengendang must be able to know the location of the mandhêg in each piece he is going to present. The main factor is the empirical factor of a controller to be able to determine the mandhêg position of each musical structure.